A Bibliometric Analysis of Reactive Oxygen Species Based Nanotechnology for Cardiovascular Diseases - Liang, Yun; Liao, Shenjie; Zhang, Xiaoshen (Frontiers in Cardiovascular Medicine, 2022)
Cardiovascular diseases (CVDs) continue to be the leading cause of health problems around the world. Because of its unique properties, reactive oxygen species (ROS)-based nanotechnology offers novel solutions to the diagnosis and treatment of CVDs. In order to identify and further promote the development of ROS-based nanotechnology in CVDs, we here provide a bibliometric analysis. 701 eligible articles about the ROS - based nanotechnology for cardiovascular disease up to May 26th, 2022, were taken from the Web of Science Core Collection database. The VOSviewer was used to analyze annual publications, countries/institutions, funding agencies, journals and research category, and the research hotspots. From the publication of the first article in 2005 to 2021, the output and the number of citations of articles are on the rise. Based on the bibliometric analysis, we found that the current research focuses on the correlation between diagnosis (sensors and), treatment (oxidative stress, inflammation and drug delivery) and safety (toxicity). Since 2019, research on nanomedicine and drug delivery has become a hotspot. So, more research in chemistry, materials, biology, and medicine is required to further develop and construct ROS-based nanomaterials.